PERBANDINGAN PENENTUAN KADAR PROKSIMAT DALAM BATUBARA MENGGUNAKAN METODE GRAVIMETRI KONVENSIONAL DAN THERMOGRAVIMETRIC ANALYSIS - Muhammad Robiansyah; Subur P. Pasaribu; Aman Sentosa Panggabean (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2021)
Research on the comparison of the determination of proximate levels in coal using conventional gravimetric methods and Thermogravimetric Analysis (TGA) through comparative tests has been carried out. This study aims to determine the comparison of the average analysis results using the t-test, the precision level of analysis results of each method using CV Horwitz, and the comparison of the precision level of the analysis results using the F test. Based on the results of the t-test showed a significant difference in the average analysis results between the two methods for all parameters. In the test using CV Horwitz for parameters of inherent moisture, volatile matter and fixed carbon using both methods and also ash content using the conventional gravimetric method was declared to meet the precision requirements, but for the ash content parameter using TGA instruments was stated otherwise. The F test for parameters of ash content and inherent moisture showed a significant difference in the precision level of the analysis results between the two methods, but for the parameters of volatile matter and fixed carbon was stated otherwise.